PENGARUH KUALITAS PRODUK, HARGA DAN KEPERCAYAAN TERHADAP MINAT BELI PRODUK FASHION SECARA ONLINE - Muhammad Hafidz Prasetyo; Hasyim, Hasyim (Nusantara Hasana Berdikari, 2022)
This study aims to obtain an overview of product quality, price and trust in buying interest in online fashion products and determine the magnitude of the influence of each variable, either simultaneously or partially. This research can be used as a quantitative approach that uses a causal relationship. The population in this study are online site users who are found in the Tangerang district. The source of the data used is qualitative data, which was obtained from respondent data through a questionnaire that was quantified through a Likert scale, the sample used was purposive sampling method. With this research, the researcher determines the sample to be taken from the students. The results showed that partially product quality and price had a significant effect on online fashion buying interest, the trust variable had no significant effect on online fashion buying interest. Simultaneous test results show that the variables of product quality, price, and trust together have a positive and significant effect on buying interest in online fashion. The determinant coefficient is 28.2%, which means that the intention to buy Fashion online can be explained by the variables of product quality, price, and trust of 28.2%, while the remaining 72.8% can be explained by other variables outside the model.